Health Literacy Is an Independent Predictor of Cancer Patients' Hospitalizations - Laura A. Cartwright; Levent Dumenci; J. Brian Cassel; Maria D. Thomson; Robin K. Matsuyama (SLACK Incorporated, 2017)
Background: Lower levels of health literacy predict higher hospitalization rates. Hospitalization is expensive and many admissions are potentially avoidable. Research examining the relationship between health literacy and health outcomes for cancer patients is limited, and no published studies to date have focused on hospitalization and health literacy in cancer patients. Objective: This study examined the ability of health literacy to predict hospitalization of cancer patients. Methods: This secondary data analysis investigated the relationship between health literacy and hospitalization rates of adult cancer patients in the first 5 years after their diagnosis. The sample included a diverse selection of cancer diagnoses and all stages of cancer were represented. Health literacy was assessed using the Cancer Health Literacy Test 30 (CHLT-30), a psychometrically sound measure of health literacy validated in a cancer patient population. Health literacy's ability to predict the number of times hospitalized, total days spent hospitalized, and number of 30-day readmissions was examined using multivariate negative binomial multiple regression to control for the outcomes and potentially confounding variables. Key Results: When controlling for potentially confounding variables, a negative relationship was found between health literacy and the number of inpatient hospitalizations (β = −0.041, p = .009) and the total number of days spent hospitalized (β = −0.028, p = .023) independently, whereas the relationship between health literacy and the number of 30-day readmissions failed to reach significance (β = −0.002, p = .903). Conclusions: Patients with lower health literacy need additional assistance to avoid unplanned hospitalizations.